The algorithm for selection of interval of parameters recalculation of control and management objects in automatic control systems of process engineering - Tynynyka, A. N. (Technology and design in electronic equipment, 2016)
The author presents an algorithm for selecting of measurements and adjusting interval of parameters of control and management objects of hierarchical ACS, packaged with a variety of technical equipment and means of communication between the components. The interval that is acceptable for fidelity of reproduction of characteristics of objects is determined using Kotelnikov theorem. The algorithm is proposed to be used as a universal sequence of actions in the implementation of the various ways to achieve optimal control. The paper shows the possibility of using the algorithm in the management of dynamic objects with predictive models.